CORAK KEAGAMAAN PESANTREN SALAFIYAH MUSTHAFAWIYAH PURBA BARU MANDAILING NATAL - Manshuruddin, Manshuruddin (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
This study purposes to describe analitically the religious paradigm of Pesantren Musthafawiyah Purba Baru (PSMPB) Mandailing Natal North Sumatera by tracing their manhaj of aqeedah, the concept of plurality and jihad. From this study, the writer found that the manhaj aqidah of the PSMPB was Ahl Sunnah wal Jama'ah - referring to the books of aqidah Asya'irah and Maturidiyah. In the school of fiqh the PSMPB is Syafi'iyah. Regarding plurality, the PSMPB recognizes that diversity in ethnicity, nation, religion, etc. is God's will, which must be accepted. However, the PSMPB firmly believes theologically that Islam is a true religion and others are heretical. Religious tolerance only applies to the ethical-social context. In the context of Jihad, the PSMPB interpreted it broadly not only in physical warfare, but also in intellectual, and social service. From this it can be understood that the religious paradigm of the PSMPB is wasathiyah.